Implementing Guided Inquiry to Improve Curiosity Of Student Learning In Biology of Class XI IPA SMA Al Muayyad Academic Year 2014/2015 - Siti Nurfauziyah; Marjono Marjono; Bowo Sugiharto (Universitas Sebelas Maret, 2015)
The purpose of this research is to improve the curiosity of students through the implementation of guided inquiry learning biology class XI IPA SMA Al Muayyad Surakarta academic year 2014/2015. This research is a class action research which consists of three cycles. Each cycle contains planning, implementing, observing and reflecting. The subjects were students of class XI SMA Al Muayyad which consisting of 15 male students and 13 female students. The data collecting techniques of this research was observation, interview, and questionnaires about the curiosity of students. Data validation was triangulation techniques. Data was analysed by qualitative descriptive analysis technique that consists of three components, namely data reduction, data presentation, and conclusion. Research procedures using spiral method. The indicators curiosity of students was interested attitude toward discussion of a matter, trying to overcome the problems and events, asking teacher and friends, participate actively in discussions, and seek information from various sources. The results show that the average percentage of achievement indicators curiosity of students based on data analysis pre-cycle are 32%, first cycle are 57%, second cycle are 70%, and third cycle are 72%. This research’s conclusion is the implementation of guided inquiry can improve the curiosity of students in biology class XI IPA SMA Al Muayyad Surakarta school academic year 2014/2015.Keywords: guided inquiry, curiosity